1966
DOI: 10.1113/jphysiol.1966.sp007904
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of cortical inhibition

Abstract: SUMMARY1. We have studied the effects of various pharmacological agents on the cortical inhibitory process described in the previous two papers (Krnjevid, Randic & Straughan, 1966a, b); the drugs were mostly administered directly by iontophoresis from micropipettes and by systemic injection (i.v.).2. Strychnine given by iontophoresis or by the application of a strong solution to the cortical surface potentiated excitatory effects, but very large iontophoretic doses also depressed neuronal firing. Subconvulsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

1970
1970
1996
1996

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(20 citation statements)
references
References 56 publications
4
13
0
3
Order By: Relevance
“…The possibility that CMZ may potentiate GABA by an interaction with such a process may be relevant to the present study as there is some evidence to suggest that GABA and glycine may share the same chloride ionophore (Barker & McBumey, 1979). Although picrotoxin is usually considered a specific OABA antagonist, there is evidence in the literature to indicate a lack of specificity (Krnjevic, Randic & Straughan, 1966;Bernardi, Marciani, Morocutti & Giacomini, 1976) and Davidoff & Aprison (1969) found picrotoxin to block responses to glycine. Thus it is possible that our results may be explained by an action at the picrotoxin recognition site.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that CMZ may potentiate GABA by an interaction with such a process may be relevant to the present study as there is some evidence to suggest that GABA and glycine may share the same chloride ionophore (Barker & McBumey, 1979). Although picrotoxin is usually considered a specific OABA antagonist, there is evidence in the literature to indicate a lack of specificity (Krnjevic, Randic & Straughan, 1966;Bernardi, Marciani, Morocutti & Giacomini, 1976) and Davidoff & Aprison (1969) found picrotoxin to block responses to glycine. Thus it is possible that our results may be explained by an action at the picrotoxin recognition site.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the report that bicuculline interferes with this cortical inhibition (Curtis & Felix, 1971) is not necessarily at variance with this proposal since it would appear that the two groups of investigators were studying the inhibitory effects of surface stimulation on different cortical neurones. Curtis & Felix (1971) limited their study to identified pyramidal tract neurones whereas Krnjevi6 et al (1966) examined the effects of surface stimulation on unidentified cortical neurones. Regarding the inhibitory pathway from cerebellar Purkinje neurones to Deiters' nucleus, available evidence strongly favours GABA as the transmitter substance involved (Curtis & Johnston, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Picrotoxin has been shown to be a potent GABA antagonist at invertebrate synapses (Robbins & van der Kloot, 1958;Takeuchi & Takeuchi, 1969;EarI & Large, 1972) and some workers have found it active on mammalian centraI neurones (Galindo, 1969;Engberg & Thaller, 1970;ten Bruggencate & Engberg, 1971;Hill et all., 1972a), whereas others have found it inactive (Krnjevic, Randic' & Straughan, 1966;Curtis, Duggan & Johnston, 1969). The reported inconsistencies of pictrotoxin as a GABA antagonist may be due to differences in technique and practical difficulties resulting from the low stability of picrotoxin solutions and the low solubility of the active picrotoxinin moiety (Bryan & Marshall, 1948;Ramwell & Shaw, 1963).…”
Section: Control Agonistsmentioning
confidence: 99%